The characterization of RNA-binding proteins and RNA metabolism-related proteins in fungal extracellular vesicles - Dallastella, Marianna; Oliveira, Willian Klassen de; Rodrigues, Marcio L.; Goldenberg, Samuel; Alves, Lysangela R. (Frontiers in Cellular and Infection Microbiology, 2023)
RNA-binding proteins (RBPs) are essential for regulating RNA metabolism, stability, and translation within cells. Recent studies have shown that RBPs are not restricted to intracellular functions and can be found in extracellular vesicles (EVs) in different mammalian cells. EVs are involved in intercellular communication and the export of various molecules. EVs released by fungi contain a variety of proteins involved in RNA metabolism. These include RNA helicases, which play essential roles in RNA synthesis, folding, and degradation. Aminoacyl-tRNA synthetases, responsible for acetylating tRNA molecules, are also enriched in EVs, suggesting a possible link between these enzymes and tRNA fragments detected in EVs. Proteins with canonical RNA-binding domains interact with proteins and RNA, such as the RNA Recognition Motif (RRM), Zinc finger, and hnRNP K-homology (KH) domains. Polyadenylate-binding protein (PABP) plays a critical role in the regulation of gene expression by binding the poly(A) tail of messenger RNA (mRNA) and facilitating its translation, stability, and localization, making it a key factor in post-transcriptional control of gene expression. The presence of proteins related to the RNA life cycle in EVs from different fungal species suggests a conserved mechanism of EV cargo packing. Various models have been proposed for selecting RNA molecules for release into EVs. Still, the actual loading processes are unknown, and further molecular characterization of these proteins may provide insight into the mechanism of RNA sorting into EVs. The discovery of RBPs in EVs suggests that RNA regulation may not be limited to the confines of the cell. Future studies will be needed to unravel the specific functions and mechanisms of RBPs in EVs and their roles in intercellular communication and RNA regulation. This work reviews the current knowledge of RBPs and proteins related to RNA metabolism in EVs derived from distinct fungi species.